Overexpression of a developing xylem cDNA library in transgenic poplar generates high mutation rate specific to wood formation - Rauschendorfer, James; Yordanov, Yordan; Dobrev, Petre; Vankova, Radomira; Sykes, Robert; Külheim, Carsten; Busov, Victor (Plant biotechnology journal, 2020)
We investigated feasibility of the Full-length complementary DNA OvereXpression (FOX) system as a mutagenesis approach in poplar, using developing xylem tissue. The main goal was to assess the overall mutation rate and if the system will increase instances of mutants affected in traits linked to the xylem tissue. Indeed, we found a high mutation rate of 17.7%, whereas 80% of all mutants were significantly affected in cellulose, lignin and/or hemicellulose. Cell wall biosynthesis is a major process occurring during xylem development. Enrichment of mutants affected in cell wall composition suggests that the tissue source for the FOX library influenced the occurrence of mutants affected in a trait linked to this tissue. Additionally, we found that FLcDNAs from mutants affected in cell wall composition were homologous to genes known to be involved in cell wall biosynthesis and most recovered FLcDNAs corresponded to genes whose native expression was highest in xylem. We characterized in detail a mutant line with increased diameter. The phenotype was caused by a poplar homolog of LONELY GUY 1 (LOG1), which encodes an enzyme in cytokinin biosynthesis and significantly increased xylem proliferation. The causative role of LOG1 in the observed phenotype was further reaffirmed by elevated cytokinin concentration in the mutant and recapitulation overexpression experiment wherein multiple independent lines phenocopied the original FOX mutant. Our experiments show that the FOX approach can be efficiently used for gene discovery and molecular interrogation of traits specific to woody perennial growth and development.
Keywords: genová knihovna; Populus; lignin; Xylem; Mutation Rate; Gene Library; xylém; buněčná stěna; Wood; poplar; fox hunting system; Gene Expression Regulation, Plant; dřevo; mutační rychlost; Plant Proteins; Lignin; genetics; regulace genové exprese u rostlin; Cell Wall; rostlinné proteiny